2007
DOI: 10.1021/es0617993
|View full text |Cite
|
Sign up to set email alerts
|

Metal Complexes and Free Radical Toxins Produced by Pfiesteria piscicida

Abstract: Metal-containing organic toxins produced by Pfiesteria piscicida were characterized, for the first time, by corroborating data obtained from five distinct instrumental methods: nuclear magnetic resonance spectroscopy (NMR), inductively coupled plasma mass spectrometry (ICP-MS), liquid chromatography particle beam glow discharge mass spectrometry (LC/PB-G DMS), electron paramagnetic resonance spectroscopy (EPR), and X-ray absorption spectroscopy (XAS). The high toxicity of the metal-containing toxins is due to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 44 publications
2
50
0
Order By: Relevance
“…The IC 50 values of LHA are over 3 orders of magnitude lower for certain lipoxygenases than cycloxygenases (Butovich and Lukyanova, 2008). Metal containing organic toxins have also been characterized and reported in the dinoflagellate, Pfeisteria piscicida (Moeller et al, 2007). Divalent metals have been shown to be cofactors that increase the toxicity of P. parvum extracts (Yariv and Hestrin, 1961;Ulitzer and Shilo, 1966), and enhanced toxicity is observed in waters with high mineral content.…”
Section: Discussionmentioning
confidence: 99%
“…The IC 50 values of LHA are over 3 orders of magnitude lower for certain lipoxygenases than cycloxygenases (Butovich and Lukyanova, 2008). Metal containing organic toxins have also been characterized and reported in the dinoflagellate, Pfeisteria piscicida (Moeller et al, 2007). Divalent metals have been shown to be cofactors that increase the toxicity of P. parvum extracts (Yariv and Hestrin, 1961;Ulitzer and Shilo, 1966), and enhanced toxicity is observed in waters with high mineral content.…”
Section: Discussionmentioning
confidence: 99%
“…Toxic strains Moeller et al, 2007) thrive in eutrophic estuaries Magnien et al, 2000;Glasgow et al, 2001); linked both directly (via nutrient uptake-experiments by Lewitus et al, 1999b;Glibert et al, 2006b) and indirectly to nutrient enrichment (experiments by Lewitus et al, 1999a;Burkholder et al, 2001a,b) +Phagotrophy (cryptophytes, other algae) while harboring cryptophyte kleptochloroplasts; +osmotrophy (urea)…”
Section: Pfiesteria Piscicidamentioning
confidence: 99%
“…This suggests that chemicals excreted from L. masanensis may inhibit feeding by S. jeokjo. Recently, Moeller et al (2007) reported the nature of toxins produced by P. piscicida (i.e. metal complexes and free radical toxins) by using 5 different analytical methods.…”
Section: Differential Feedingmentioning
confidence: 99%